2015
DOI: 10.1016/j.apcata.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the visible-light photoactivity of Bi2WO6 using acidic carbon additives

Abstract: a b s t r a c tWe have explored the role of the physicohemical properties of carbon materials as additives to bismuth tungstate on its structure, optical properties, and photocatalytic activity for the degradation of rhodamine B under visible light. For this purpose, C/Bi 2 WO 6 hybrid composites were prepared following two different routes: (i) physical mixture of the catalyst components, and (ii) one-pot hydrothermal synthesis of the semiconductor in the presence of the carbon additive. Three carbons with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The spectra corresponding to the WO 3 /carbon mixtures showed similar trends regardless of the crystalline phase of WO 3 ; below 500 nm the profiles were similar to those of the corresponding bare semiconductor. In the region between 500-800 nm, the absorbance gradually increased with the amount of the carbon additive ( Figure S1), as a result of the light absorption of the carbon matrix [43,44].…”
Section: A) B)mentioning
confidence: 99%
“…The spectra corresponding to the WO 3 /carbon mixtures showed similar trends regardless of the crystalline phase of WO 3 ; below 500 nm the profiles were similar to those of the corresponding bare semiconductor. In the region between 500-800 nm, the absorbance gradually increased with the amount of the carbon additive ( Figure S1), as a result of the light absorption of the carbon matrix [43,44].…”
Section: A) B)mentioning
confidence: 99%
“…On the contrary, the dependence with the structural order of the carbon additive is not clear, as previously discussed for the conversion of phenol (Figures 5 and 6). A similar behavior has been reported for the degradation of RhB using other semiconductors, and attributed to the degradation via coupled mechanisms (photosensitization, photocatalysis, and carbon-photon mediated reactions) in acidic photocatalysts (Galoppini, 2004;Carmona et al, 2015;Wang et al, 2014). Indeed, acidic catalysts' surfaces favor strong interactions with the adsorbed RhB molecules, boosting the degradation via the photosensitization as a result of a more efficient injection of electrons from the dye to the surface of the catalyst.…”
Section: Rhodamine B Photodegradationmentioning
confidence: 52%
“…20 nm in the absorption sharp edge was detected as the samples are prepared by physical mixture; it is unlikely (but may not be discarded) to have an optimized interface between both phases of this catalyst that would favor the absorption of low energy photons. However, the profiles of the WO3/carbon catalysts showed a marked increase in the absorbance in the region between 500 and 800 nm, regardless the nature of the carbon, a characteristic feature associated with the strong light absorption of black opaque materials (Araña et al, 2003;Carmona et al, 2015). The trend for the absorption above 500 nm followed the order: CNT > HC > CL.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Various forms of porous carbons have also been used for this purpose, due to the increased mass transfer upon adsorption of the pollutant on the porosity [21,22]. In this regard, recent investigations including our own have reported that the photocatalytic performance of Bi 2 WO 6 can be enhanced by the use of certain amounts of carbon additives; nevertheless, the effect of the carbon additive has been barely addressed, and the optimum nominal carbon content seems to be unclear and dependent on the nature of the carbon additive [23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%